Performance of a modified, three-step menstrual cycle tracking method in naturally cycling females - Doroshuk, M. L.; Doyle-Baker, P. K. (International Journal of Kinesiology & Sports Science, 2025)
Background: An objective method of menstrual cycle tracking while minimizing participant burden and cost for field-based research is needed. A modification was proposed to a well-known three-step (m3-step) method to improve accessibility for participants and athletes with difficult travel schedules.